2014
DOI: 10.1073/pnas.1413825111
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of SUMO sites and analysis of SUMOylation changes induced by external stimuli

Abstract: SUMOylation is an essential ubiquitin-like modification involved in important biological processes in eukaryotic cells. Identification of small ubiquitin-related modifier (SUMO)-conjugated residues in proteins is critical for understanding the role of SUMOylation but remains experimentally challenging. We have set up a powerful and highthroughput method combining quantitative proteomics and peptide immunocapture to map SUMOylation sites and have analyzed changes in SUMOylation in response to stimuli. With this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(176 citation statements)
references
References 41 publications
11
165
0
Order By: Relevance
“…In accordance with the His 6 precipitation data presented here, previous reports suggest that only SUMO1 is conjugated to EXOSC10; multiple mass spectrometry analyzes of affinity tagged SUMO1 conjugates, but not SUMO2 or SUMO3, identified EXOSC10 as a SUMO target (Zhao et al 2004;Matic et al 2010;Westman et al 2010;Impens et al 2014;Lamoliatte et al 2014). In accordance with this, a screen of the endogenous SUMOylated proteome identified EXOSC10 conjugation to SUMO1 but not SUMO2 (Becker et al 2013).…”
Section: Implications Of Exosc10 Sumoylationsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with the His 6 precipitation data presented here, previous reports suggest that only SUMO1 is conjugated to EXOSC10; multiple mass spectrometry analyzes of affinity tagged SUMO1 conjugates, but not SUMO2 or SUMO3, identified EXOSC10 as a SUMO target (Zhao et al 2004;Matic et al 2010;Westman et al 2010;Impens et al 2014;Lamoliatte et al 2014). In accordance with this, a screen of the endogenous SUMOylated proteome identified EXOSC10 conjugation to SUMO1 but not SUMO2 (Becker et al 2013).…”
Section: Implications Of Exosc10 Sumoylationsupporting
confidence: 92%
“…Reports of dynamic changes in EXOSC10 expression are not extensive, however it has been shown that yeast EXOSC10 is destabilized by deletion of its binding partner Rrp47 (C1D in humans) and in human cell lines by the chemotherapeutic 5-fluorouracil Feigenbutz et al 2013). Interestingly, EXOSC10 has previously been identified in screens of SUMOylation (Zhao et al 2004;Golebiowski et al 2009;Westman et al 2010;Becker et al 2013;Impens et al 2014;Tammsalu et al 2014). This presents the possibility that the increased SUMOylation in the cold participates in regulation of EXOSC10 (Fig.…”
Section: Exosc10 Is Sumoylated By Sumo1 But Not Sumo2mentioning
confidence: 99%
See 2 more Smart Citations
“…The yeast MRX complex serves as a positive regulator of sumoylation, and sumoylation significantly promotes the DDR in this system (40). Ribet and colleagues also recently reported the use of HeLa cell lines that stably express His 6 -SUMO1-T95R and His 6 -SUMO2-T91R and use of the PTMScan ubiquitin remnant motif antibody to identify cellular proteins constitutively conjugated to SUMO1 or SUMO2 (41). That analysis identified 295 SUMO1-conjugated peptides in 227 substrate proteins and 167 SUMO2-conjugated sites in 135 substrate proteins.…”
Section: Discussionmentioning
confidence: 99%